An Uncommon Intramedullary Tumor: Primary Spinal Cord Melanoma - Çetinalp, Nuri Eralp (Korean Society of Spine Surgery, 2014)
A 47-year-old woman was admitted with complaints of progressive weakness in the lower extremities and pain in the back and left leg. Thoracic magnetic resonance imaging (MRI) revealed a spinal intramedullary tumor between the T9 and L1 levels, which were iso- to hypointense on T2 and slightly hyperintense on T1-weighted images. The tumor was resected as total, and the diagnosis was malignant melanoma confirmed with histopathology. Neurological findings improved at the postoperative period and no residual or recurrence was noted on postoperative MRI at the 9-month follow-up. Primary melanoma of the spinal cord, particularly intramedullar localization, is seldomly reported in the literature. We report a primary malignant melanoma of the spinal cord and emphasize the diagnostic and prognostic challenges.